Optimization of bioethanol production using oil palm frond juice - Lawanya, K. Ramu (2015)
This paper presents the optimum conditions for producing bioethanol using oil palm frond juice. Bioethanol has been gaining much interest recently in terms of research and development. Since there are various factors such as rising oil price, environmental issues and high rate consumption of fossil fuel, the global demand for bioethanol has shown a remarkable increase. Oil palm frond is known to be the most generated oil palm biomass annually. OPF is obtained during pruning for harvesting fresh fruit bunch, and the juice can be produced by pressing the fresh OPF using the conventional sugarcane pressing machine. The OPF juice contains higher glucose content, which is about 70% of the total free sugar. Hence, it has a high potential to be the carbon source for producing bioethanol. The parameters investigated in this research work are temperature, pH and agitation speed. Bioethanol was produced from oil palm frond juice by fermentation with Saccharomyces cerevisiae. The ethanol concentration from the fermentation sample was analysed using HPLC. Using the ethanol concentration obtained from HPLC analysis, the optimum condition for the production of bioethanol was determined using the Response Surface Methodology with the aid of Design Expert software. The results revealed that, a maximum bioethanol concentration of 22.93 g/L can be obtained at the following optimum conditions : temperature of 32°C, pH 6 and agitation speed of 80 rpm. The validation result revealed that at this optimum condition, a bioethanol yield of 30.1% , which is close to the predicted value, can be obtained.